FAKTOR YANG MEMPENGARUHI HASIL BELAJAR SELAMA BDR PADA MASA COVID-19 DI KECAMATAN TANGSE - Yusuf, Bustami; Amaliah, Mutia; Musfikar, Rahmat (UNIKU PRESS, 2024)
ABSTRACTDuring the COVID-19 pandemic, large-scale activities were restricted, including in the world of education, which issued a policy requiring students to study from their homes, including schools in rural areas. During the COVID-19 pandemic, this study was conducted to determine the conditions for implementing learning from home in rural schools. The study was carried out at SMAN 1 Tangse and MAN 6 Pidie in Kecamatan Tangse, Kabupaten Pidie, Aceh, with the participation of four teachers and 152 class XII students from both schools. The quantitative method is used, with descriptive data analysis and multiple linear regression using the SmartPLS 3 program, to determine the conditions of BDR implementation by examining the influence of perceptions, media, methods, and learning constraints on learning outcomes. Based on the analysis of the data obtained, it can be concluded that the implementation of BDR is categorized as